Caregivers' impression about the effect of subthalamic nucleus deep brain stimulation in the treatment of parkinson's disease - Değirmenci, Yıldız; Tezcan, Sabiha; Savaş, Ali; Akbostancı, Muhittin Cenk (Turkish Neurosurgical Society, 2023)
AIM: To determine caregivers' impressions of the impact of STN-DBS on motor and non-motor symptoms of Parkinson's disease (PD) in patients who underwent subthalamic nucleus deep brain stimulation (STN-DBS), evaluate the relationship of these changes with disease characteristics, and examine their contribution to the daily lives of patients. MATERIAL and METHODS: The caregivers of patients who underwent STN-DBS were interviewed over the telephone. All telephone interviews were recorded, and changes in the motor and non-motor symptoms of the patients after STN-DBS were evaluated with a standardized questionnaire. RESULTS: Of the 173 patients with PD who underwent STN-DBS between 2005 and 2015, 62 who could be contacted by telephone were enrolled in the study. The mean age of the patients was 59.71 +/- 9.78 years (range: 33-77 years). The mean disease duration was 15.62 +/- 8.66 years (Range: 4-50 years). STN-DBS was performed on average 3.88 +/- 2.6 years earlier (range: 1-11 years). According to the caregivers of the patients, there was a reduction in "off" periods in 79% of the patients, tremor in 58.1%, dyskinesia in 59.6%, depression in 46.8 %, pain symptoms in 41.9%, and improvement in sleep problems in 43.6% after STN-DBS. Moreover, 80.6% of the patients reported an improvement in their daily life activities after STN-DBS. CONCLUSION: From the caregivers' perspective, there was an improvement in the non-motor symptoms as well as the motor symptoms of patients with PD after STN-DBS, and this had a positive effect on the activities of daily lives in the majority of patients. Telephone interviews can be considered as an alternative method in the follow-up of patients with PD, especially when they cannot be assessed face-to-face.
Keywords: Parkinson’s Disease; DBS; Caregiver Impression